In-beam study of 144Gd - Mariscotti, M. A. J.; Beuscherc, H.; Davidsonc, W. F.; Gonoc, Y.; Jägerc, H. M.; Liederc, R. M.; Müller-Veggianc, M.; Neskakisc, A.; Haennic, D. R.; Zolnowski, D. R. (North-Holland Publishing Company, 1978)
Fil: Mariscotti, M. A. J. Comisión Nacional de Energía Atómica; Argentina